KEBIJAKAN PEMERINTAH DALAM PENANGGULANGAN KEKERASAN TERHADAP ANAK DI TENGAH PANDEMI COVID-19 - Luth Luth; Rani Maswati; Meriwijaya Meriwijaya (Jurnal Caraka Prabu, 2022)
The Covid-19 pandemic has had a negative impact, namely the number of children being victims of violence. Based on data from the Online Information System for the Protection of Women and Children, cases of violence against children in the midst of the Covid-19 pandemic experienced a significant increase. The purpose of this study is to find out government policies in overcoming violence against children in the midst of the covid 19 pandemic. This type of research is an approach that is carried out by literature studies in scientific journals, books, documents, websites, and other sources. The results showed that the government through the ministry of women's empowerment and child protection (PPPA) issued several policies in the form of the Joint Movement to Take Care of Our Families, Optimizing the role of Community-Based Integrated Child Protection (PATBM) activists, Opening telephone service for women and children's friends (SAPA) 192, and Issuing Government Regulation (PP) Number 78 of 2021 concerning Special Protection for Children.